Performance enhancement strategies of a hybrid solar chimney power plant integrated with photovoltaic panel - Pratap singh, A.; Kumar, A.; Akshayveer; Singh, O.P. (Elsevier Ltd, 2020)
This paper examines the possibility of integrating a photovoltaic (PV) module in a hybrid solar chimney power plant (HSCPP). Since HSCPP is a greenhouse thermal buoyancy-driven system, the surrounding high temperature environment makes PV module temperature extremely high resulting in lower electrical conversion efficiency. Various design configurations of collector duct and solar chimney are investigated using an experimentally validated numerical model to study the PV panel cooling and turbine power output. The results show that turbine power output is sensitive to diverging the chimney up to maximum static pressure recovery limit while PV module shows marginal increase in electrical efficiency. Converging the collector duct alone shows worst turbine and PV module performance. However, in case of combine designs of converging duct and divergent chimney, considerable improvement of PV panel efficiency (about 7%) was observed. The results show that about 80% of the collector area measured from the chimney axis are the most effective region for cooling the PV module where consistent temperature drop of 10–12 °C was observed. A design map vs. PV panel efficiency has been shown charting future directions for designing such energy efficient hybrid solar chimney systems. © 2020 Elsevier Ltd
Keywords: Hybrid solar chimney power plant (HSCPP); Photovoltaic; Computational Fluid Dynamics (CFD); Tapered collector; Divergent chimney; Taper ratio